Accurate Antemortem Diagnosis of Equine Protozoal Myeloencephalitis (EPM) Based on Detecting Intrathecal Antibodies against Sarcocystis neurona Using the SnSAG2 and SnSAG4/3 ELISAs. (26th August 2013) - Reed, S.M.; Howe, D.K.; Morrow, J.K.; Graves, A.; Yeargan, M.R.; Johnson, A.L.; MacKay, R.J.; Furr, M.; Saville, W.J.A.; Williams, N.M.
<x xml:space="preserve">Abstract</x> Background Recent work demonstrated the value of antigen‐specific antibody indices (AI and C‐value) to detect intrathecal antibody production against Sarcocystis neurona for antemortem diagnosis of equine protozoal myeloencephalitis (EPM). Objectives The study was conducted to assess whether the antigen‐specific antibody indices can be reduced to a simple serum : cerebrospinal fluid (CSF) titer ratio to achieve accurate EPM diagnosis. Animals Paired serum and CSF samples from 128 horses diagnosed by postmortem examination. The sample set included 44 EPM cases, 35 cervical‐vertebral malformation (CVM) cases, 39 neurologic cases other than EPM or CVM, and 10 non‐neurologic cases. Methods Antibodies against S. neurona were measured in serum and CSF pairs using the SnSAG2 and SnSAG4/3 (SnSAG2, 4/3) ELISAs, and the ratio of each respective serum titer to CSF titer was determined. Likelihood ratios and diagnostic sensitivity and specificity were calculated based on serum titers, CSF titers, and serum : CSF titer ratios. Results Excellent diagnostic sensitivity and specificity was obtained from the SnSAG2, 4/3 serum : CSF titer ratio. Sensitivity and specificity of 93.2 and 81.1%, respectively, were achieved using a ratio cutoff of ≤100, whereas sensitivity and specificity were 86.4 and 95.9%, respectively, if a more rigorous cutoff of ≤50 was used. Antibody titers in CSF also provided good diagnostic accuracy. Serum antibody titers alone yielded much lower sensitivity and specificity. Conclusions and Clinical Importance The study confirms the value of detecting intrathecal antibody production for antemortem diagnosis of EPM, and they further show that the antigen‐specific antibody indices can be reduced in practice to a simple serum : CSF titer ratio.